155 CHARACTERISTICS AND PREDICTORS OF INPATIENT FALLS IN A GERIATRIC REHABILITATION UNIT. (18th November 2021) - Smyth, H; O'Connor, A; O'Connor, S; Mello, S
Abstract: Background: Falls are one of the most frequent complications on geriatric rehabilitation wards. In addition to having adverse consequences for patients, falls also result in prolonged hospitalisation and increased healthcare costs. Therefore, identification of risk factors and development of successful falls prevention strategies targeted at this population are essential. The aim of this study is to identify predisposing or situational risk factors contributing to falls in older adults completing post-acute inpatient rehabilitation. Methods: Retrospective review of all inpatient falls on two geriatric rehabilitation units over a one year period identified from incident forms. Chi-squared test was used to calculate differences between fallers and non-fallers. Results: One in five patients admitted to the unit suffered a fall (average age 81, 52% male) with a total of 95 falls involving 56 patients. Of these, only 77% (n = 43) were identified as high risk on falls screening. 61% (n = 34) had one fall and 39% (n = 22) had two or more falls. Nearly one in three (n = 15) falls resulted in injury. More falls occurred in the single bedded unit (14.8 per 1, 000 bed-days) as compared to the multi-bedded unit (6.8 per 1, 000 bed days). Use of a Zimmer frame or rollator was associated with more falls than use of other mobility aids. Fallers tended to have a previous history of falls (75%, n = 42) and polypharmacy (average 10 medications). Delirium and dementia were present in one third of fallers. Falls were associated with a higher risk of discharge to long-term care, with 70% of fallers discharged home compared to 89% of non-fallers (p = 0.0006). Conclusion: Previous falls, single room occupancy, polypharmacy and a medium level of dependency when mobilizing were identified as predictors of falls in our review. Nearly a quarter of fallers were not identified as high falls risk on screening further questioning the utility of falls risk screening assessments.